Veterinary euthanasia techniques : a practical guide - Cooney, Kathleen; Chappell, Jolynn; Callan, Robert J.; Connally, Bruce A. (Hoboken : John Wiley & Sons, 2012)
Veterinary Euthanasia Techniques: A Practical Guide provides detailed guidance on euthanasia procedures in a wide variety of species, including dogs, cats, exotics, horses, and production animals. Based on the current AVMA guidelines, the book offers step-by-step descriptions of the recommended methods of euthanasia, giving all the information needed to perform these techniques with confidence. Veterinary Euthanasia Techniques helps practitioners, students, and technicians expand their knowledge base and provide competent, compassionate euthanasia services. Including information on client cons.
The presence of onlookersThe type and amount of euthanasia solution available; The signalment and physical condition of the animal; The need for a postmortem examination; Inhalant methods; Injectable methods; Physical methods; Species-specific techniques; Dogs and cats; Exotics; Horses; Livestock; Noninhalant pharmaceutical agents; Unacceptable methods for domestic animals; Death and associated signs; Chapter 6 Body Aftercare; Burial; Composting; Cremation/incineration; Rendering; Species-specific considerations; Dogs and cats; Exotics; Horses; Livestock; Conclusion; Bibliography.
Web ReferencesIndex.
Print version record.
Keywords: Euthanasia of animals -- Technique -- Handbooks, manuals, etc; Veterinary anesthesia -- Handbooks, manuals, etc; Animals, Domestic; Euthanasia of animals -- Technique; Euthanasia, Animal -- methods; Veterinary anesthesia; Agriculture; MEDICAL -- Veterinary Medicine -- Food Animal; MEDICAL -- Veterinary Medicine -- Small Animal; Electronic books